Radiological Kinetics of Brain Metastases and Clinical Implications for Patients Treated With Stereotactic Radiosurgery. Issue 1 (January 2019) - Nicholls, L.W.; Pinkham, M.B.; Bernard, A.; Lusk, R.; Watkins, T.; Hall, B.; Olson, S.; Foote, M.C.
Abstract: Aims: Select patients with brain metastases receive stereotactic radiosurgery (SRS) with the objective of improving survival and intracranial disease control. Brain metastases number and volume are prognostic factors used to inform patient selection. The aim of this study was to assess the rate of change of brain metastases size and number (growth kinetics) between the diagnostic and day of SRS magnetic resonance imaging (MRI) scans. Materials and Methods: All patients treated with Gamma Knife SRS between October 2015 and April 2017 were included in this single-centre retrospective analysis. Brain metastases number and diameter were recorded at diagnosis and treatment. For patients with multiple brain metastases, the largest lesion was the index lesion. Distant intracranial control and overall survival were reported from the date of SRS. Results: In total, 146 patients received 156 episodes of SRS. The median interval between diagnostic and SRS MRI was 20 days (range 1–68). Interval growth in the index lesion of at least 3 mm or the development of a new brain metastasis was noted in 60.2% of patients. This was associated with age less than 60 years ( P = 0.001), Eastern Cooperative Oncology Group (ECOG) performance status 2 or above ( P = 0.04), non-small cell lung carcinoma (NSCLC) ( P = 0.03) or melanoma histologies ( P = 0.05) and uncontrolled extracranial disease ( P = 0.05). These patients were also more likely to develop distant intracranial recurrence ( P = 0.046). Clinically significant growth was not associated with scan interval or differences in overall survival. The Kaplan–Meier estimate of probability of survival at 12 months was 59.3% (95% confidence interval 46.7–75.2%) for all patients. Conclusion: Intracranial progression between diagnosis and day of SRS is common. Risk factors are uncontrolled extracranial disease, poorer performance status, NSCLC or melanoma histologies and age less than 60 years. These patients would benefit from an MRI closer to treatment to inform patient selection and target delineation for SRS planning. Highlights: Significant intracranial progression between diagnosis and radiosurgery treatment is common. Interval growth of at least 3mm or the development of a new brain metastasis occurred in 60% of patients. Faster intracranial growth was associated with young age, poor performance status and uncontrolled extracranial disease. Patients with significant intracranial progression were more likely to develop distant intracranial recurrence.